2017
DOI: 10.1192/bjpo.bp.116.004382
|View full text |Cite
|
Sign up to set email alerts
|

Postinjection delirium/sedation syndrome in patients with schizophrenia receiving olanzapine long-acting injection: Results from a large observational study

Abstract: BackgroundPostinjection delirium/sedation syndrome (PDSS) has been reported uncommonly during treatment with olanzapine long-acting injection (LAI), a sustained-release formulation of olanzapine.AimsThe primary aim of the study was to estimate the incidence per injection and per patient of PDSS events in adult patients with schizophrenia who were receiving olanzapine LAI in real-world clinical practice. Secondary aims were to further characterise the clinical presentation of PDSS events, to identify potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
5
18
1
Order By: Relevance
“…The safety profile of SGA-LAIs, such as olanzapine, aripiprazole, risperidone, and PP, are generally analogous to OAPs,79 except for the post-injection delirium/sedation syndrome with olanzapine LAI 114. Other side-effects include variable incidences of psychotic symptoms, EPS events, and metabolic/endocrine-related TEAEs (weight gain, hyperprolactinemia, and impaired glucose metabolism) 115.…”
Section: Review Of Evidencementioning
confidence: 99%
“…The safety profile of SGA-LAIs, such as olanzapine, aripiprazole, risperidone, and PP, are generally analogous to OAPs,79 except for the post-injection delirium/sedation syndrome with olanzapine LAI 114. Other side-effects include variable incidences of psychotic symptoms, EPS events, and metabolic/endocrine-related TEAEs (weight gain, hyperprolactinemia, and impaired glucose metabolism) 115.…”
Section: Review Of Evidencementioning
confidence: 99%
“…In Romania, LAIs are usually initiated in psychiatric departments and they were administered in psychiatry hospitals, during day admissions, for better monitoring the patients. Moreover, olanzapine- LAI requires a period of minimum 3 h of medical monitoring after administration, and a family member must accompany the patient home (these measures are imposed for the prevention of post- injection delirium/sedation syndrome) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has a weak effect on mental illness with negative symptoms. 17 Guo et al found that olanzapine combined with escitalopram was better than olanzapine alone in the treatment of schizophrenia with depression. 18 Paroxetine is mostly used to treat depression patients with anxiety disorder.…”
Section: Discussionmentioning
confidence: 99%